Mediterranean Diet and Type 2 Diabetes Mellitus: A Perpetual Inspiration for the Scientific World. A Review - Tatjana Milenkovic; Nadica Bozhinovska; Djuro Macut; Jalica Bjekic-Macut; Dario Rahelic; Zelija Velija Asimi; Azra Burekovic (My University, 2021)
For the past 80 years, the effect of the Mediterranean diet on overall health has been a constant topic of interest among medical and scientific researchers. Parallel with the persistent global rise of cases of type 2 diabetes, many studies conducted in the past 20 years have shown the benefits of the Mediterranean lifestyle for people with, or at risk of developing, type 2 diabetes mellitus. However, despite the large body of evidence, concerns exist amongst scientists regarding the reliability of the data related to this topic. This review offers a glimpse of the onset of the Mediterranean diet and follows its significant impact on the prevention and treatment of type 2 diabetes. There is a constant rise in type 2 diabetes cases on the Balkan Peninsula and North Macedonia in particular. Having in mind that North Macedonia, as well as most of the countries on the Balkans have low to middle income, there is a need for a certain affordable dietary pattern to ameliorate the rise in diabetes incidence, as well as improve the glycemic control. We did a review based on the available literature regarding Mediterranean diet and people with or at risk of developing type 2 diabetes mellitus, its effects on glycemic control, lipid profile and metabolic outcome.
Keywords: type 2 diabetes mellitus; Mediterranean diet; obesity; insulin resistance; prediabetes